Upright Balance Control in Individuals with Cervical Myelopathy Following Cervical Decompression Surgery: A Prospective Cohort Study - Cheng, Chih-Hsiu; Lai, Dar-Ming; Lau, Phooi Yee; Wang, Shwu-Fen; Chien, Andy; Wang, Jaw-Lin; Hsu, Wei-Li (Scientific reports, 2020)
Patients with cervical myelopathy may manifest impairments in functional activities and balance control caused by compression of the spinal cord. The objective of the current study was to determine long-term changes in the upright balance control of patients with cervical myelopathy who had undergone cervical decompression surgery. This is a prospective cohort study from the preoperative phase to 3 months, 6 months, and 1 year postsurgery. Fifty-three patients with cervical myelopathy were recruited for the cervical myelopathy group and 22 age-matched healthy controls were recruited for the control group. Functional assessments including Japanese Orthopedic Association Cervical Myelopathy Evaluation Questionnaire-Lower Extremity Function (JOACMEQ-LEF) and 10-second step test; as well as balance assessments including postural sway (center-of-pressure: COP) were performed for both groups. The JOACMEQ-LEF (p = 0.036) scores of the myelopathy group improved postoperatively, and a significant decrease in COP variables of postural sway was observed. The upright posture was less stable in the myelopathy group than in the control group (p < 0.05) both before and after surgery. The effect size and standard response mean of the COP variables ranged from −0.49 to 0.03 at 3 months, 6 months, and 1 year postsurgery. The upright balance control had improved significantly 6 months after decompression surgery. However, the balance control of the patients who had undergone decompression surgery remained less stable than that of the age-matched healthy controls. Balance training should be initiated before 6 months postsurgery to accelerate balance control recovery in patients with cervical myelopathy.